Portfolio Choice in Retirement—What is The Optimal Home Equity Release Product?. Issue 2 (24th February 2015) - Hanewald, Katja; Post, Thomas; Sherris, Michael
Abstract: We study the decision problem of the optimal choice between home equity release products from a retired homeowner's perspective in the presence of longevity, long‐term care, house price, and interest rate risk. The individual can choose to release home equity using reverse mortgages or home reversion plans, to buy annuities, and long‐term care insurance. The individual enjoys utility gains from having access to either one of the two equity release products. Higher utility gains are found for the reverse mortgage, as its product features allow for higher lump‐sum payouts and provide downside protection for house prices.